2015
DOI: 10.1016/j.biocon.2014.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Free and open-access satellite data are key to biodiversity conservation

Abstract: Satellite remote sensing is an important tool for monitoring the status of biodiversity and associated environmental parameters, including certain elements of habitats. However, satellite data are currently underused within the biodiversity research and conservation communities. Three factors have significant impact on the utility of remote sensing data for tracking and understanding biodiversity change. They are its continuity, affordability, and access. Data continuity relates to the maintenance of long term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
187
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(200 citation statements)
references
References 21 publications
0
187
0
13
Order By: Relevance
“…For our study, this required sampling 6 years with >150 images over a 20-year time frame, which would not have been possible without free, high-quality medium-resolution image data. Ongoing Landsat and Sentinel missions extend the archive of freely-available, mediumresolution, full-range optical data (Turner et al, 2015), which will be invaluable to support microrefugia detection and many other applications of Earth observation data to conservation and environmental management. Although the Landat TM, Landsat-8 OLI, and Sentinel-2 sensors sample slightly different wavelength bands, with careful calibration and co-registration of images, it should be possible to detect microrefugia with time series of multi-sensor data, expanding the temporal extent of similar analyses, and enabling them into the future.…”
Section: Discussionmentioning
confidence: 99%
“…For our study, this required sampling 6 years with >150 images over a 20-year time frame, which would not have been possible without free, high-quality medium-resolution image data. Ongoing Landsat and Sentinel missions extend the archive of freely-available, mediumresolution, full-range optical data (Turner et al, 2015), which will be invaluable to support microrefugia detection and many other applications of Earth observation data to conservation and environmental management. Although the Landat TM, Landsat-8 OLI, and Sentinel-2 sensors sample slightly different wavelength bands, with careful calibration and co-registration of images, it should be possible to detect microrefugia with time series of multi-sensor data, expanding the temporal extent of similar analyses, and enabling them into the future.…”
Section: Discussionmentioning
confidence: 99%
“…Costello et al, 2013aCostello et al, , 2014Dicks et al, 2014;Turner et al, 2015;Wetzel et al, 2015;Stephenson et al, in press Metrics of use collated and reported (3.7) Technologies used regularly to obtain and integrate user feedback, ensuring an iterative approach to development. Regular reports produced to provide internal and external feedback on progress toward targets set out by the knowledge product's business plan.…”
Section: Undp 2009; Mcinerny Et Al 2014mentioning
confidence: 99%
“…Mapping land cover and monitoring land cover change are important for a variety of societal and scientific purposes, including land management, natural resource management, ecological studies, sustainable development, climate modeling, urban planning, habitat monitoring, and many others [1][2][3][4][5]. The U.S Geological Survey (USGS) is moving forward with a Land Change Monitoring, Assessment, and Projection (LCMAP) initiative to develop an expanded operational capacity for land cover mapping and monitoring to support these needs.…”
Section: Introductionmentioning
confidence: 99%